The Decision Of Waiheru Village Women To Work In The Informal Sector (Case Study Of Women Traders In Waiheru Market) - Vivi Angga Rifka Rifai; Aphrodite M. Sahusilawane; Noviar F. Wenno (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to determine the reasons and influence of age, education level, husband's income, number of family dependents, and social environment on the decision of female traders to work in the informal sector as traders. The sample used was purposive sampling technique with a total sample of 45 female traders. The results showed that women in Waiheru village decided to work in the informal sector as market traders because of household needs, self-will, lack of other skills, and others. This is based on factors that are taken into consideration in women's decision-making to work in the informal sector, namely age, education level, husband's income, number of family dependents and social environment. Age influences the decision of women in Waiheru Village to work as traders because women of productive age are able to contribute to meeting household needs, have good memory and are more willing to take risks. The level of education influences because being a trader does not require a high education. However, with the education that women have, they can make good decisions, have trading skills, add insight, be able to manage their business and innovate about the business or merchandise they are running. Husband's income influences the decision of Waiheru women to work as traders because women feel that they also have responsibilities in the home to fulfill the needs of the household and the needs for themselves. Family dependents influence because it has a positive impact in order to meet daily needs. The social environment influences because it is a supporting factor for women's decisions as traders, but some of them also feel unaffected because this is their own desire without coercion from others.